Association Between Plasma Amyloid-β and Neuropsychological Performance in Patients With Cognitive Decline - Yun, Gyihyaon; Kim, Hye Jin; Kim, Hyug-Gi; Lee, Kyung Mi; Hong, Il Ki; Kim, Sang Hoon; Rhee, Hak Young; Jahng, Geon-Ho; Yoon, Sung Sang; Park, Key-Chung; Hwang, Kyo Seon; Lee, Jin San (Frontiers in Aging Neuroscience, 2021)
Objective: To investigate the association between plasma amyloid-β (Aβ) levels and neuropsychological performance in patients with cognitive decline using a highly sensitive nano-biosensing platform. Methods: We prospectively recruited 44 patients with cognitive decline who underwent plasma Aβ analysis, amyloid positron emission tomography (PET) scanning, and detailed neuropsychological tests. Patients were classified into a normal control (NC, n = 25) or Alzheimer’s disease (AD, n = 19) group based on amyloid PET positivity. Multiple linear regression was performed to determine whether plasma Aβ (Aβ40, Aβ42, and Aβ42/40) levels were associated with neuropsychological test results. Results: The plasma levels of Aβ42/40 were significantly different between the NC and AD groups and were the best predictor of amyloid PET positivity by receiver operating characteristic curve analysis [area under the curve of 0.952 (95% confidence interval, 0.892–1.000)]. Although there were significant differences in the neuropsychological performance of cognitive domains (language, visuospatial, verbal/visual memory, and frontal/executive functions) between the NC and AD groups, higher levels of plasma Aβ42/40 were negatively correlated only with verbal and visual memory performance. Conclusion: Our results demonstrated that plasma Aβ analysis using a nano-biosensing platform could be a useful tool for diagnosing AD and assessing memory performance in patients with cognitive decline.